Evaluating the combined effect of a systemic phenylpyrrole fungicide and the plant growth‐promoting rhizobacteria Paraburkholderia phytofirmans (strain PsJN:gfp2x) against the grapevine trunk pathogen Neofusicoccum parvum. Issue 11 (6th July 2020) - Wu, Hanxiang; Spagnolo, Alessandro; Marivingt‐Mounir, Cécile; Clément, Christophe; Fontaine, Florence; Chollet, Jean‐François
Abstract: BACKGROUND: A new chemical control strategy for grapevine trunk diseases (GTDs) is to develop site‐targeted fungicides to protect grapevine vascular tissues. Due to the complexity of GTDs, the effectiveness of a single method is limited. Investigation of the interactions between chemical and biological agents is an essential requirement for integrated control strategies. The effect of a phloem‐mobile derivative of the fungicide fenpiclonil (SM 26) in combined use with the plant growth‐promoting rhizobacteria, Paraburkholderia phytofirmans PsJN on the Neofusicoccum parvum strain Bourgogne (NpB) was evaluated. RESULTS: SM 26 was found to be translocated to the shoot apices and roots of grapevines through both xylem and phloem after foliage application. In vitro studies demonstrated that SM 26 exhibited no inhibitory effect on the growth of PsJN and could be largely absorbed into the bacterial cells. In vivo evaluation showed that the combined use of SM 26 and PsJN was the most effective following artificial inoculation of NpB on the stems of rooted Chardonnay and Sauvignon cuttings. Finally, the expression of defence‐related genes, including the genes associated with secondary metabolism ( ANTS, PAL, STS, Vv17.3 ), defence proteins ( GLUC, PR1, PGIP ), redox status ( GTS1 ) and ethylene synthesis ( ACC ), was found to be strongly upregulated in PsJN + SM 26 cotreated plants compared to non‐treated plants (controls), especially for Chardonnay. CONCLUSION: The systemic profungicide SM 26 interacts with the biocontrol agent PsJN to stimulate some plant defence responses, and their combined use may present a potential integrated control strategy against GTDs. © 2020 Society of Chemical Industry Abstract : The combined use of a plant growth‐promoting rhizobacteria and a phloem‐mobile profungicide can activate grapevine immune responses and result in the highest control efficiency against Neofusicoccum parvum strain Bourgogne. © 2020 Society of Chemical Industry